The Advaitic Experience in Christianity and Hinduism : Comparing Jacques Dupuis’ Discernment about Jesus’ Awareness with Saradananda’s Notes on Sri Ramakrishna’s Mystical Experience - Toar Banua Hutagalung (Indonesian Journal of Theology, 2014)
Relationality between Jesus the Son and God the Father becomes a perfect model of God and humanity. But, how do we understand the meaning of this relationality? Why in Hinduism, especially, in Advaitic tradition, this relationality issue becomes an essential element to realize the one God? Can we do a pilgrimage of our faith by comparing Christian and Hindu traditions? This study will examine on mystical approach of Sri Ramakrishna’s experience as a Hindu and the discernment of Jacques Dupuis’ on awareness as a Catholic. The notion of relationality would be exposed within those two different traditions, each with different perspectives. One will question Advaita and the other will delve into awareness. In the end, advaitic perspectives will help us to comprehend the relationality of God and humanity through our readings of understanding Dupuis’ awareness.